1997
DOI: 10.1007/s004410050849
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis induced by methylazoxymethanol in developing rat cerebellum: organization of the cell nucleus and its relationship to DNA and rRNA degradation

Abstract: We present a cytological and biochemical study of the cell death of granule cell precursors in developing rat cerebellum following treatment with the cytotoxic agent methylazoxymethanol (MAM) during the first postnatal week. The density of apoptotic figures per square millimeter progressively increases after 6, 12, 24 and 44 h of treatment, whereas cells immunoreactive for proliferating cell nuclear antigen tend to disappear in the external granular layer (EGL). DNA migration on gel electrophoresis reveals a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…A rearrangement of RNPs in cells of the developing rat cerebellum has been described by Lafarga and coworkers (Lafarga et al, 1997) following treatment with the cytotoxic (arrows) is densely packed and forms spherical areas typical of nucleolar segregation. e) gold immunolabeling for DNA on the condensed chromatin (C); the nucleolus (asterisk) is surrounded by and intermingled with nucleoplasmic RNPs (arrowheads).…”
Section: Nucleoplasmic and Nucleolar Rnps In Apoptosismentioning
confidence: 80%
See 2 more Smart Citations
“…A rearrangement of RNPs in cells of the developing rat cerebellum has been described by Lafarga and coworkers (Lafarga et al, 1997) following treatment with the cytotoxic (arrows) is densely packed and forms spherical areas typical of nucleolar segregation. e) gold immunolabeling for DNA on the condensed chromatin (C); the nucleolus (asterisk) is surrounded by and intermingled with nucleoplasmic RNPs (arrowheads).…”
Section: Nucleoplasmic and Nucleolar Rnps In Apoptosismentioning
confidence: 80%
“…A rearrangement of RNPs in cells of the developing rat cerebellum has been described by Lafarga and coworkers (Lafarga et al, 1997) following treatment with the cytotoxic Clevenger and Epstein, 1984) after incubation with an undiluted MoAb (ICN Pharmaceuticals, Italy), and with an Alexa 488-conjugated goat anti-mouse IgG (Molecular Probes). a) control cells; b,c) cells treated with 20 µM DRB for 5 h and for 24 h, respectively: the discretely dotted immunolabeling of controls becomes progressively more diffuse with increasing treatment time.…”
Section: Nucleoplasmic and Nucleolar Rnps In Apoptosismentioning
confidence: 93%
See 1 more Smart Citation
“…They frequently appeared detached from the nuclear envelope and exhibited a fine granular texture (Fig. 2E), corresponding to the cross-section of closely packed chromatin fibers (32).…”
Section: Resultsmentioning
confidence: 99%
“…59,61,62 However, recent reports revealed that both the 28S rRNA and the 18S rRNA are cleaved in several cell lines during apoptosis. 63 Interestingly, it has also been reported that the mitochondrial 16S rRNA molecule can be cleaved after apoptotic stimulation. 64 The apoptotic cleavage sites in rat 28S rRNA have been mapped to the two largest divergent domains, D2 (approx.…”
Section: The 28s Rrna Molecule Is Cleaved During Apoptosismentioning
confidence: 99%